Alfonso X, the Learned, Cantigas de Santa Maria. An Anthology. Ed. de Stephen Parkinson. Modern Humanities Research Association. Critical Text. Volumen 40, 2015 - González, Déborah (Revista de Poética Medieval, 2019)
Reseña del libro: Alfonso X, the Learned, Cantigas de Santa Maria. An Anthology. Edición de Stephen Parkinson. Mondern Humanities Research association. Critical Text. Vol. 40, 2015, 161 pp.